CRIMINAL LAW FORMULATION POLICIES RELATED TO CORPORATE CRIME - I Kadek Darma Santosa (Program Studi PPKn Universitas Pendidikan Ganesha, 2020)
The role of corporations today dominates daily life, especially with the increasing needs of the community. It's no longer a country that provides needs, but corporations. Corporations can increase state wealth and labor, but the revolutionary economic and political structure has caused great corporate power, so that the state can be influenced in accordance with its interests. Based on this background, a problem arises namely how the policy of formulation of criminal law enforcement so far for corporations that commit criminal acts as well as how the policy of formulation of criminal law in dealing with corporate criminal acts in the future. The research method used in this study is normative juridical using secondary data. Data collection is done by collecting and analyzing relevant library materials. Furthermore, the data are analyzed in a qualitative normative manner by interpreting and constructing statements contained in documents and legislation. The conclusion of this research is the regulation of sanctions regarding inconsistent corporate criminal acts. Inconsistencies in determining or imposing maximum fines imposed on corporations, there is no uniformity in determining when a corporation can be said to have committed a crime, regarding who can be held accountable or prosecuted and convicted, and the formulation of types of criminal that can be imposed on the corporation that commits criminal act.